Exercise Reverses the Alterations in Gut Microbiota Upon Cold Exposure and Promotes Cold-Induced Weight Loss - Meng, Yan; Chen, Lina; Lin, Wentao; Wang, Hongjuan; Xu, Guoqin; Weng, Xiquan (Frontiers in Physiology, 2020)
Altered gut microbiota contributes to reduced diet-Induced obesity (1) and orchestrates energy homeostasis upon cold exposure (2). Exercise also modify the gut microbiome and reduce the overweight (3). However, the composition of the gut microbiome in relation to cold exercise combining have not been systematically examined. We explore the effects of combination of room temperature, acute cold, intermittent cold, sustained cold and exercise( each n = 5) on the high-fat diet obesity rats following 4 visits at day (0;1;3;35). And compared the white fat browning, weight loss, cardiovascular effects, gut microbiota change among groups. Sustained cold exercise showed the largest marked shift of the microbiota. Unexpected exercise reverse the alterations of gut microbiota alpha-diversity and a few phyla upon cold exposure (Proteobacteria decreased upon cold but increased upon cold exercise) and at the same time up-regulated much more white fat browning level, get more weight loss and prevents the negative cardiovascular effects of cold exposure. And correlation analysis shows that cold exercise related gut microbial communities significantly correlate with the white fat browning and cardiovascular phenotypes. These results could be a novel mechanism via which interaction healthy effect imparted by cold exercise was achieved by interaction altered gut microbe.